Analisis Indikator Gaya Hidup Yang Berhubungan Dengan Usia Menarche Remaja Putri - Dina - Safitri; Arneli - Wati; Erwin - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to determine the lifestyle indicators that related to menarche age of female teenagers. The methodology that used in this research was correlational studies (association relationship) with retrospective approach. The population in this research was all female student in junior high school in Pekanbaru that have been menarche. This research was conducted on 98 female students in 9 junior high schools in Pekanbaru spread over 3 districts in Pekanbaru. Samples were taken from junior high school that the location was in district with cluster sampling method and then simple random sampling method. The tools used questionnaire that the validity and reliability had been tested. The analysis used univariate and bivariate. The univariate analysis explained respondent characteristic and the variable view. The bivariate analysis explained correlation between each variable with chi-square test. The results that there was relationship between exercise habits and stress control with menarche age of female teenagers, with p value is 0,000 and 0,009. For indicators of diet and bed rest showed that there was no relationship with menarche age. Expected for female teenagers can behave in healthy living lifestyle, especially for exercise habits and stress control that related with menarche age. Keywords: lifestyle indicators, menarche age, female teenager.